STRATEGIES DE GESTION DES CADRES ET CONDITIONS DE VIE DES POPULATIONS A ABOBO - Bernard, Eviar Ohomon; Koffi, Atta; Téré, Gogbe (European Scientific Journal, ESJ, 2013)
﻿﻿In recent years, the Ivorian government has made improving frameworks of living a priority. Thus was created the Ministry of urban sanitation. Unfortunately, the implementation of policies and strategies for managing solid waste and wastewater is a problem in the city of Abidjan in general and particularly in the Abobo causing degradation of managers and living conditions of people in this county. This study analyzed the main strategies for waste management (solid and liquid ) established by the people of the common objective in Abobo seen to improve their management and living conditions. To do this, an analysis of the overall approach to solid waste management systems and wastewater management by the people was made. Thus, two approaches to solid waste management are adopted by the people of the town. This is the formal management by dealers and informal management or management companies door provided by precollectors door. Precollection door to door is the preferred management as practiced by the people of the town garbage. This system will remove about 76 tons of garbage per day. This low rate of pre-collection is explained by the lack of adequate and appropriate equipment. The pre-fetched quantities are dumped into garbage bins on the sidewalks, in the wild or in places deposits waves. Regarding the wastewater management, two services are used by households. It is the collective system of autonomous t or individual system. Nearly 79.44 % of the population uses the individual system for the disposal of their wastewater. This system raises the issue of product management for emptying septic tanks. These products are not managed in a sanitary manner and causing diseases and degradation of executives and living In view of the foregoing , it is recommended that the State and local authorities are involved benefit in the management of waste ( solid and liquid) in the municipality to improve the management and living conditions of populations this common Abidjan device.